Exploring in vitro anti-proliferative and anti-inflammatory activities of Prasachandaeng remedy, and its bioactive compounds - Nuntika Prommee; Arunporn Itharat; Pakakrong Thongdeeying; Sunita Makchuchit; Weerachai Pipatrattanaseree; Adis Tasanarong; Buncha Ooraikul; Neal M. Davies (BMC, 2022)
Abstract Background Prasachandaeng (PSD) remedy has been empirically used in Thai traditional medicine to treat fever in bile duct and liver and cancer patients through Thai folk doctors. However, there have been no scientific reports on the bioactive compounds and bioactivities related to inflammation-associated carcinogenesis or cytotoxicity against cancer cell lines. In this study, we investigated the chemical content of the remedy, and evaluated its cytotoxic activity against two cancer cell lines in comparison with a non-cancerous cell line and determined tumor necrosis factor-alpha (TNF-α) production in a murine macrophage cell line (RAW 264.7) to evaluate anti-inflammatory activity. A novel HPLC method was used for quality control of its chemical content. Methods Pure compounds from the EtOH extract of D. cochinchinensis were isolated using bioassay-guided fractionation and chemical content of the PSD remedy was determined using HPLC. The cytotoxic activity against the hepatocarcinoma cell line (HepG2) and cholangiocarcinoma cell line (KKU-M156), in comparison with non-cancerous cell line (HaCaT), were investigated using antiproliferative assay (SRB). The anti-inflammatory activity measured by TNF-α production in RAW 264.7 was determined using ELISA. Results All crude extracts and isolated compounds exhibited significant differences from vincristine sulfate (**** p < 0.0001) in their cytotoxic activity against HepG2, KKU-M156, and HaCaT. The PSD remedy exhibited cytotoxic activity against HepG2 and KKU-M156 with IC50 values of 10.45 ± 1.98 (SI = 5.3) and 4.53 ± 0.74 (SI = 12.2) µg/mL, respectively. Some constituents from C. sappan, D. cochinchinensis, M. siamensis, and M. fragrans also exhibited cytotoxic activity against HepG2 and KKU-M156, with IC50 values less than 10 µg/mL. The isolated compounds, i.e., Loureirin B (1), 4-Hydroxy-2,4'-dimethoxydihydrochalcone (2), and Eucomol (3) exhibited moderate cytotoxicity against two cancer cell lines. None of the crude extracts and isolated compounds showed cytotoxicity against HaCaT. D. cochinchinensis and PSD remedy exhibited higher anti-inflammatory activity measured as TNF-α production than acetaminophen. Conclusion The findings provide evidence of bioactivity for EtOH extracts of PSD remedy and the isolated compounds of D. Cochinchinensis. The results consistent the use clinical activity and use of PSD remedy as a antipyretic treatment for liver and bile duct cancer patients by Thai traditional practitioners.